Electroacupuncture for acute postoperative pain during coughing after video-assisted thoracoscopic surgery: study protocol for a pilot randomized controlled trial - Dan-Tong Zhang; Guang-Xia Shi; Jin-Ying Jia; Feng-Wei Tan; Yu Qi; Wei Liang; Zhi-Jun Zhao; Ping Yuan; Ya Gao; Guo-Chao Zhang; Xue-Hui Liu; Jing-Wen Yang; et al. (PLoS ONE, 2025)
Background Despite the use of multimodal analgesia regimens following video-assisted thoracoscopic surgery (VATS), acute postoperative pain persists. Electroacupuncture (EA) may alleviate acute postoperative pain following VATS; however, current evidence remains insufficient. Objectives This trial will assess the feasibility and efficacy of EA as an adjunctive treatment compared with sham electroacupuncture (SA) for managing acute postoperative pain during coughing after VATS. Study design and methods In this pilot randomized controlled trial, 60 patients with non-small-cell lung cancer who will undergo VATS will be randomly assigned to either the EA or SA group in a 1:1 ratio. Patients will receive standard care combined with four sessions of EA or SA within 72 h after surgery. The primary outcome will be the average postoperative pain score during coughing, measured using a numeric rating scale within 72 h after surgery. Secondary outcomes will include the average daily pain scores at rest, during coughing, and while mobilizing; incidence of chronic post-surgical pain; quality of life; cough symptom score; and analgesic consumption. All adverse events will be recorded in detail. Discussion This study will determine whether EA as an adjunctive treatment can reduce acute postoperative pain during coughing following VATS. Trial registration ClinicalTrial.gov ITMCTR2024000170 (http://itmctr.ccebtcm.org.cn/zh-CN/Home/ProjectView?pid=f1a344f7-7e06-4665-ad9d-0917d588eba6).